Primary Nutrients Status of Three Vermicomposts Produced in a Nigerian Sahel Region - Mahmud Sani; Alhassan Ibraheem; Sufiyanu Sani; Aliyu Abdulkadir; Ibrahim Hassan; Zara Musa; Musab Ibrahim (Bulgarian Journal of Soil Science, 2024)
A pot experiment was conducted at the soil and water laboratory of Federal University Gashua Nigeria, to assess the reaction and primary nutrients – NPK, and Organic Carbon (OC) status of three white grub-produced Vermicompost using different ingredients (Municipal Waste – MW, Typha Grass – TP, and Municipal Waste + Typha Grass – MWT0). Laid on a Completely Randomized Design (CRD), the number of live worms, worms' weight, Vermicompost weight, and worms' mortality percentage as production indices were recorded and statistically analyzed upon Vermicompost maturity. Matured Vermicompost Reaction (pH and EC) and Primary nutrients (NPK), and OC were determined in another laboratory upon taking the respective compost samples as Soil health Indices. The result of the analysis showed that MW has the highest Nitrogen (%) = 1.60, the highest available Phosphorus = 0.47 mgKg-1, and the highest Exchangeable Potassium = 720 mgKg-1, it also presented a mildly acidic reaction (pH=6.8), with the highest percentage of OC (2.80%) and the lowest basic salts EC = 0.35 dS/m. In terms of earlier determined live worm percentage, live worm weight, Vermicompost weight, and worm mortality rate, the highest findings are MW = 64.5 %, MW = 40 grams, MW = 301 grams, and TP = 66.9 % respectively. In conclusion, MW Vermicompost proves to be the best, taking into consideration its better indices. As the premier of its kind in the study area, among other recommendations, we encourage setting this study as a pilot, and the conduct of more studies on the efficiency of Vermicompost on soil health and crop production in the study area.